A new species of Rhinophis Hemprich, 1820 (Serpentes: Uropeltidae) from the central hills of Sri Lanka - Wickramasinghe, L. J. Mendis; Vidanapathirana, Dulan Ranga; Rajeev, M. D. Gehan; Gower, David J. (Zootaxa, 2017)
A new species of uropeltid snake, Rhinophis roshanpererai sp. nov., is described based on three specimens from Badulla District, Sri Lanka. The new species is distinguished from its congeners by the number of dorsal scale rows and ventral scales, a colour pattern that lacks pale stripes, and by having a very small tail shield with four or three prominent spines. Based on lack of records from similar habitats and elevations elsewhere in Sri Lanka, the new species likely has a very small range in the central highlands. The description of the new species brings the total nominal species of Rhinophis to 20, with four of the 16 Sri Lankan species having been described since 2009.